2019
DOI: 10.3390/ijms20235863
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of the YABBY Transcription Factor Family in Pineapple and Functional Identification of AcYABBY4 Involvement in Salt Stress

Abstract: The plant-specific transcription factor gene family, YABBY, belongs to the subfamily of zinc finger protein superfamily and plays an essential regulatory role in lateral organ development. In this study, nine YABBY genes were identified in the pineapple genome. Seven of them were located on seven different chromosomes and the remaining two were located on scaffold 1235. Through protein structure prediction and protein multiple sequence alignment, we found that AcYABBY3, AcYABBY5 and AcYABBY7 lack a C2 structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 36 publications
2
34
0
Order By: Relevance
“…The phylogenetic tree showed that the YABBY genes can be divided into five groups (CRC/DL, INO, FIL, YAB2, and YAB5), but orchid YABBY genes are only found in four clades and absent in the YAB5 clade, which exclusively comprises YABBY genes of basal angiosperms and eudicots. It has been reported that monocot species, including rice and pineapple, also do not contain YAB5 -like genes [ 41 ]. De Almeida et al [ 42 ] studied the comparative development of the androecial form across the Zingiberales and found one YABBY2 gene, which was also less homologous to YAB5 .…”
Section: Discussionmentioning
confidence: 99%
“…The phylogenetic tree showed that the YABBY genes can be divided into five groups (CRC/DL, INO, FIL, YAB2, and YAB5), but orchid YABBY genes are only found in four clades and absent in the YAB5 clade, which exclusively comprises YABBY genes of basal angiosperms and eudicots. It has been reported that monocot species, including rice and pineapple, also do not contain YAB5 -like genes [ 41 ]. De Almeida et al [ 42 ] studied the comparative development of the androecial form across the Zingiberales and found one YABBY2 gene, which was also less homologous to YAB5 .…”
Section: Discussionmentioning
confidence: 99%
“…“Vegetative” YABBY genes were also shown to act as transcriptional activators of jasmonate-triggered responses [ 89 ]. Consistent with a role in the jasmonate response, recent studies have revealed some new functions of YABBY TFs in the response to abiotic stress (salt, heat, and drought stress response) in pineapple, soybean, grapevine, pomegranate, and cotton [ 51 , 61 , 90 , 91 , 92 , 93 ], leaf curling [ 94 , 95 ], and in the delay of the flowering stage [ 95 ].…”
Section: Expression Patterns and Putative Functions Of Members Of The Yabby Gene Familymentioning
confidence: 97%
“…Hormone responsive elements were the most abundant, including auxin (IAA), gibberellin (GA), salicylic acid Plant growth and development are affected by various environmental stresses. Therefore, it is important to study the cis-acting elements associated with environmental stress [34]. In this study, 88 elements were related to environmental stress, including 25 lowtemperature-responsive elements, 10 defense-and stress-responsive elements and 53 elements essential for anaerobic induction.…”
Section: Calculation Of Tahat Duplication Eventsmentioning
confidence: 99%